KARAKTERISTIK POHON INANG ANGGREK DI KAWASAN TAMAN NASIONAL LORE LINDU (Studi Kasus Desa Mataue, Kecamatan Kulawi, Kabupaten Sigi) - Murtiningsih, Ika; Ningsih, Sri; Muslimin, Muslimin (Jurnal Warta Rimba, 2016)
Orchidacea is a family of fower plant having varous amount of species.  It was estimated to have about 15,000 – 20,000 species.  Orchids can grow not only in the tropics and sub tropics but also grow in various range of altitudes. Besides that, orchids are also known to grow as epiphyt as well as on the soil, rocks and marsh and all are called terrestrial orchid.   The largest distribution of orchids is found in the tropical rain forest.  The objectives of this research was to study the characteristics of host trees for orchids naturally grown at Mataue Village, Lore Lindu National Park.  The method used was line transect (four lines) each with 200 m in length.  Each line consisted of five plots with the size of 20 m x 20 m and the distance between plots was 20 m.  The total number of observaion plots were 20.  The result of the research revealed that the host trees includes Arenga pinnata, Macaranga sp, Syzigium sp, Colophyllum sp, Canarium sp, Cyathea sp, Ficus sp, Glochidion lucidum sp, Lithocarpus sp, Engelhardtia serrata Blume dan Durio zibethinus Merr. The aforementioned host trees have general characteristics inciluding big stem, cracked and hard bark, some of them have peeled off and coarse bark.  Specific to Macaranga sp and Glochidium lucidum, orchids grow om the lower part of the tree and have sufficient amout of solar radiation.Keywords:  host tree, orchids, Lore Lindu National Park